Ancistrothyrsus scopae (Passifloraceae), a new species from Amazonian Brazil and Guyana, with keys to the genus and species - Feuillet, Christian (Phytotaxa, 2020)
A third species is described in Ancistrothyrsus (Passifloraceae) from Amazonas (Brazil) and Guyana. The new species, A. scopae, is characterized by young stem trichomes of two kinds, the longer ones being up to 5 mm long and branched like bottlebrushes. The two previously described species do not have bottlebrush trichomes. A key to the South American genera of tribe Passifloraceae s. str. and a key to the species of Ancistrothyrsus are presented.